The Potentials of Goodness and Badness in Humans on the Qur'an and Hadith - Nuraini Nuraini; Eduwar Eduwar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Goodness and badness are two terms that are widely used to determine an action done by humans. All forms of human action refer to them views on goodness and badness. The value of goodness and badness will always be a source of reference in carrying out various actions in their life. Goodness and badness values are not only in philosophical studies, but also become the focus of discussion on various religious sources, including the Qur’an and Hadith. Specifically this research is directed to find out the potential in humans, in this case it is closely related to the potential goodness and badness in humans which are explained in the Qur’an and Hadith. In the QS. al-Shams: 8 stated that there is a balance of the potential of  goodness and badness in humans, but in the hadith of Imam Bukhari No. 1385 stated that the potential of goodness is the most prominent in humans since being born in a state of nature. Based on these differences, the problem arises in this research that are how the views of the interpreters in interpreting verses and hadiths about the potential of goodness and badness in humans, and how to make the potential of goodness for more involved than bad. This study aims to determine the opinion of the intrepreters and find out the reasons of each intrepreter in talking about the potential of goodness and badness in humans. The results showed that the potential of goodness is the most prominent in humans, also obtained a sign that in essence the positive potential of humans is stronger than the negative potential, it's just that the attraction of badness is stronger than the attraction of goodness, therefore humans are required to maintain the purity of the soul (nafs). So that the potential of goodness is more prominent than the badness, humans should guide this potential with some instructions that have been conveyed by Allah in the Qur’an, and so have been conveyed by the Prophet in the hadith, namely by keeping the heart to remain in nature.